Carpal tunnel syndrome in Iraqi paraplegic patients - Alwan, Basim M. (Journal of the Faculty of Medicine Baghdad, 2012)
Background: The median nerve in paraplegic patients, who must rely on increased hand activities including transfer and wheel-chair propulsion, may be subjected to increased pressure, so that the incidence of carpal tunnel syndrome (CTS) may be higher than that in the normal population.Objectives: To study the prevalence and the severity of carpal tunnel syndrome in Iraqi paraplegic patients and to identify the effect of duration of the injury as a possible factor related to its occurrence to avoid any chronic problems which interfere with the hand functions since these patients are greatly dependent on their hands for their daily activities.Patients and Methods: Fifty paraplegic patients (100 hands), whose level of spinal cord injury was below D2, and fifty normal control subjects were included in this study. All patients studied in this work had complete spinal cord injury and were stabled medically and neurologically.Clinical examination for the signs and symptoms of CTS as well as nerve conduction studies were carried out in both median and ulnar nerves for their sensory and motor components eliciting values for distal latencies for all patients and the control groups.Results: Thirty percent of the paraplegic patients (15 patients) had signs and symptoms consistent with carpal tunnel syndrome (CTS), and all of them had electrodiagnostic confirmation of this injury.Seventy percent of these paraplegic patients (35 patients) had no signs and symptoms suggestive of CTS, and only nearly about forty eight percent (17 patients) of them had only electrodiagnostic confirmation of CTS. Overall, 64% of the 50 paraplegic patients had CTS (32 patients). Nine paraplegic patients (18%) exhibiting bilateral CTS. Eight paraplegic patients (16%) had abnormal electrophysiological findings involving the ulnar nerve at the wrist and all of them had electrophysiological findings of CTS.There was a sharp increase in incidence of occurrence of CTS from 6.3% in the group 1 to 5 years from injury to 13.7% in the group 6 to 10 years, and to 25% in the group 11 to 15 years, and again a very big increase to 50% in the group 16 years and over from injury.Conclusion: Early testing of the median and ulnar nerve function, even in asymptomatic patients within the first 5 years of the injury, is recommended so for early detection, preventive and/or curative measures to be undertaken considering the fact that these patients are greatly dependent on their hands for their daily activities.